2020
DOI: 10.1002/ddr.21642
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of oxaceprol‐loaded poly‐lactide‐co‐glycolide nanoparticles for the treatment of osteoarthritis

Abstract: Oxaceprol is well-defined therapeutic agent as an atypical inhibitor of inflammation in osteoarthritis. In the present study, we aimed to develop and characterize oxaceprol-loaded poly-lactide-co-glycolide (PLGA) nanoparticles for intra-articular administration in osteoarthritis. PLGA nanoparticles were prepared by doubleemulsion solvent evaporation method. Meanwhile, a straightforward and generally applicable high performance liquid chromatography method was developed, and validated for the first time for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… [ 141 ] PNPs PLGA Oxaceprol Slow release In vitro - The in vitro drug release from these nanoparticles showed a sustained release of oxaceprol over 30 days. [ 149 ] PLGA Diacerein Slow release In vitro & vivo Synoviocytes; Rats The in vitro studies revealed that DIA/PLGA NPs dose-dependently suppressed mRNA levels of pro-inflammatory cytokines and enzymes; In vivo studies have showed that intra-articular injection of DIA-PLGA nanoparticles could significantly reduce the mRNA level of the above pro-inflammatory factors, increase the mRNA level of anti-inflammatory cytokines (IL-4 and IL-10), and effectively prevent cartilage degeneration. [ 150 ] PLA KGN Improve drug bioavailability; Slow release In vitro & vivo Synoviocytes; Mice Polymer microparticles showed an extended drug release of 62% over 3 months; In vitro, these particles did not change the mitochondrial activity of cultured human osteoarthritis synovial cells.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
See 1 more Smart Citation
“… [ 141 ] PNPs PLGA Oxaceprol Slow release In vitro - The in vitro drug release from these nanoparticles showed a sustained release of oxaceprol over 30 days. [ 149 ] PLGA Diacerein Slow release In vitro & vivo Synoviocytes; Rats The in vitro studies revealed that DIA/PLGA NPs dose-dependently suppressed mRNA levels of pro-inflammatory cytokines and enzymes; In vivo studies have showed that intra-articular injection of DIA-PLGA nanoparticles could significantly reduce the mRNA level of the above pro-inflammatory factors, increase the mRNA level of anti-inflammatory cytokines (IL-4 and IL-10), and effectively prevent cartilage degeneration. [ 150 ] PLA KGN Improve drug bioavailability; Slow release In vitro & vivo Synoviocytes; Mice Polymer microparticles showed an extended drug release of 62% over 3 months; In vitro, these particles did not change the mitochondrial activity of cultured human osteoarthritis synovial cells.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Several studies report significantly improved and sustained drug release using PNPs for drug delivery. PLGA, 149 , 150 polylactic acid (PLA), 151 polyurethane, 152 different polymer combinations, 153 silk fibroin, 154 and polymer-grafted mesoporous silica 155 used to prepare PNPs for drug delivery. These formulations reportedly provide improved and sustained drug-release profiles for celecoxib, curcumin, and KGN by IA drug delivery.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Alarçin et al prepared PLGA particles loaded with the anti-inflammatory drug oxaceprol (OXC) [82]. OXC is N-acetyl-L-hydroxyproline, which inhibits the inflammatory cascade by preventing granulocyte and leukocyte infiltration into joints and decreases the adherence of leukocytes to the blood vessel endothelium [158,159].…”
Section: Poly(lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%
“…It has been extensively studied for the development of devices for the controlled delivery of macromolecules. PLGA particles loading Rapamycin were already described (Alarcin et al, 2020;Butoescu et al, 2009;Gerwin et al, 2006;Haeri et al, 2018;Jung et al, 2020;Kapoor et al, 2015;Riffault et al, 2015;Zerrillo et al, 2019;Zhang and Huang, 2012). For example, Dhanabalan et al (Dhanabalan et al, 2020) described Rapamycin microparticles' cytocompatibility on the human chondrocyte cell line (C28/I2, used as a model cell line for studying normal and pathological cartilage repair mechanisms related to chondrocyte biology and physiology).…”
Section: Cytotoxicitymentioning
confidence: 99%